Prediction of sales using Big data analytics - Karthika, I.; Gokulraj, P.; Saravanan, S. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Social media is a main source of collecting big-data. Data analysis converting their bigger data to smart data. Smart data is acquired with the help of Apache Flume, Apache hive and Apache HDFS, smart data increase the sales of Marketing industry. It helps product owner to analyze people’s opinion about their product and consumer can analyze the reviews of product before purchase. If tweets came along with Location, data analyzed based on the location.